2016
DOI: 10.2116/analsci.32.1347
|View full text |Cite
|
Sign up to set email alerts
|

Adamantane-based Bidendate Metal Complexes in Crystalline and Solution State

Abstract: Bidentate organic molecules with imidazole or benzimidazole moieties connected to a rigid 1,3-diphenyladamantane spacer are simple and unique building blocks that facilitate the assembly of supramolecular architectures in the solid state via metal-coordination. Single-crystal X-ray analysis revealed that the complexation of bidentate ligand-bearing imidazole moieties with cobalt(II) or cadmium(II) ions in methanol/chloroform produced complexes that showed doublyinterpenetrated two-dimensional (2D) sheets throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…For instance, in the case of methanol, ε r value is equal to 32.62 at 25°C, but reaches 37.91 at 0°C 4 . The low temperature conditions in CSI‐MS made its use relevant for the investigation of the solution structure of organometallic compounds, 5–8 the studies of protein–ligand interactions, 9 the characterization of supramolecular assemblies, or the evidence of biomolecular aggregation species 5,10–18 . In most of these publications, this is the very low temperature of the solution infusing the metal capillary that would maintain the assemblies of non‐covalent complexes or favor the aggregation of analyzed molecules during the spray formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the case of methanol, ε r value is equal to 32.62 at 25°C, but reaches 37.91 at 0°C 4 . The low temperature conditions in CSI‐MS made its use relevant for the investigation of the solution structure of organometallic compounds, 5–8 the studies of protein–ligand interactions, 9 the characterization of supramolecular assemblies, or the evidence of biomolecular aggregation species 5,10–18 . In most of these publications, this is the very low temperature of the solution infusing the metal capillary that would maintain the assemblies of non‐covalent complexes or favor the aggregation of analyzed molecules during the spray formation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of methanol, ε r value is equal to 32.62 at 25 C, but reaches 37.91 at 0 C. 4 The low temperature conditions in CSI-MS made its use relevant for the investigation of the solution structure of organometallic compounds, [5][6][7][8] the studies of protein-ligand interactions, 9 the characterization of supramolecular assemblies, or the evidence of biomolecular aggregation species. 5,[10][11][12][13][14][15][16][17][18] In most of these publications, this is the very low temperature of the solution infusing the metal capillary that would maintain the assemblies of non-covalent complexes or favor the aggregation of analyzed molecules during the spray formation. However, to our knowledge, it does not exist any studies reported in the literature for evaluating the cooling effect of a CSI source on the ions emitted in the gas phase of the desolvation region of a mass spectrometer, when this ionization technique replaces an ESI source, where the infusing capillary and the intermediate pressure zone can be usually warm-up until 250 C and 100 C, respectively.…”
mentioning
confidence: 99%
“…The CSI method has been namely used for characterizing the structures of labile inorganic and organometallic compounds in solution or investigating labile solution structures of biomolecules such as DNA 28–31 . The use of CSI‐MS analysis in coordination chemistry allows for discriminating between no‐covalent complexes in solution whether they are discrete or oligomeric coordination species 32–34 . It has also been shown that CSI MS as NMR spectroscopy and X‐ray crystallography allows to study the formation of large‐scale aggregated chain structures or clusters in solution through intermolecular hydrogen bonds 35 …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] The use of CSI-MS analysis in coordination chemistry allows for discriminating between nocovalent complexes in solution whether they are discrete or oligomeric coordination species. [32][33][34] It has also been shown that CSI MS as NMR spectroscopy and X-ray crystallography allows to study the formation of large-scale aggregated chain structures or clusters in solution through intermolecular hydrogen bonds. 35 To our knowledge, the CSI MS has never been used to disclose no-covalent structures that can characterize a DES such as reline.…”
Section: Introductionmentioning
confidence: 99%